Microbiological quality of lettuce (Lactuca sativa) irrigated with wastewater in Addis Ababa, Ethiopia and effect of green salads washing methods - Woldetsadik, D.; Drechsel, Pay; Keraita, Bernard N.; Itanna, F.; Erko, B.; Gebrekidan, H. (Springer, 2017)
Background: In Addis Ababa, where irrigation water for vegetable production is commonly derived from the highly polluted Akaki river, information on microbial contamination of water and irrigated vegetable is scanty. An assessment was done to determine the microbiological quality of irrigation water and lettuce harvested from 10 urban farming sites of Addis Ababa. The efficacy of 5 lettuce washing methods were also assessed. A total of 210 lettuce and 90 irrigation water samples were analyzed for faecal coliform and helminth eggs population levels. Results: The mean faecal coliform levels of irrigation water ranged from 4.29-5.61 log10 MPN 100 ml-1, while on lettuce, the concentrations ranged from 3.46-5.03 log10 MPN 100 g-1. Helminth eggs and larvae were detected in 80% of irrigation water and 61% of lettuce samples. Numbers ranged from 0.9-3.1 eggs 1000 ml-1 and 0.8-3.7 eggs 100 g-1 wet weight for irrigation water and lettuce, respectively. The helminth eggs identified included those of Ascaris lumbricoides, Hookworm, Enterobius vermicularis, Trichuris trichiura, Taenia and Strongloyides larvae. Ascaris lumbricoides and Hookworm were most prevalent in both irrigation water and lettuce samples. Compared with the WHO recommendations and international standards, the faecal coliform and helminth eggs levels in irrigation water and lettuce samples exceeded the recommended levels. Irrespective of the tested washing methods, faecal coliform and helminth eggs levels were somehow reduced. Among the washing methods, potable tap water washing - rinsing (2 min) followed by dipping in 15 000 ppm vinegar solution for a minute supported the highest faecal coliorm reduction of 1.7 log10 units, whereas lowest reduction of 0.8 log10 units was achieved for the same procedure without vinegar. Conclusion: Compared with international standards, both faecal coliform and helminth eggs levels exceeded recommended thresholds in water and lettuce, but still in a potential risk range which can be easily mitigated if farmers and households are aware of the potential risk. Aside preventing occupational exposure, potential risk reduction programs should target households which have so far no guidance on how best to wash vegetables. The result of the present study suggest that the vinegar based washing methods are able to reduce faecal coliform towards low level while the physical washing with running water may help to substantially decrease potential risk of helminth parasitic infections.